Does legalization of prostitution increase human trafficking? - Cho, Seo-Young; Dreher, Axel; Neumayer, Eric (Discussion papers, 2011)
This paper investigates the impact of legalized prostitution on human trafficking inflows. According to economic theory, there are two opposing effects of unknown magnitude. The scale effect of legalizing prostitution leads to an expansion of the prostitution market, increasing human trafficking, while the substitution effect reduces demand for trafficked women as legal prostitutes are favored over trafficked ones. Our empirical analysis for a cross-section of up to 150 countries shows that the scale effect dominates the substitution effect. On average, the legalization of prostitution increases human trafficking inflows.
Keywords: Arbeitspapier; Graue Literatur